Prediction of human exposure and health risk assessment to trihalomethanes in indoor swimming pools and risk reduction strategy. Issue 8 (17th November 2019) - Abbasnia, Abbas; Ghoochani, Mahboobeh; Yousefi, Nader; Nazmara, Shahrokh; Radfard, Majid; Soleimani, Hamed; Yousefi, Mahmood; Barmar, Somayeh; Alimohammadi, Mahmood
ABSTRACT: Exposure to disinfection by-products can occur through various pathways such as inhalation, dermal contact, and ingestion for swimmers. In the present study, swimming exposure to disinfection by-products through ingestion and dermal route at the indoor swimming pool was assessed and health risks caused by exposure to these compounds were studied. Water samples were first collected from Eslamshahr (Tehran, Iran) and water quality parameters were analyzed. Then, a multi-pathway model was conducted to assess and estimate the chronic daily intakes (CDI) and lifetime cancer risk (LTCR). The results showed that the mean values of CDIs for chloroform, DCBM, DBCM, and bromoform were 2.12 × 10 −6, 7.35 × 10 −7, 8.12 × 10 −9, and 1.28 × 10 −8 mg/kg-d, respectively through ingestion pathways, and 3.95 × 10 −5, 1.56 × 10 –6, 1.88 × 10 –8, and 3.08 × 10 −8 mg/kg-d through the dermal pathway, respectively. Also our findings showed that the mean of total LTCR for swimmers was 4.63 × 10 −8 and the cancer risks through dermal route were higher than ingestion route. Also, cancer risks of chlorinated compounds were higher to implement a set of strategies in order to improve water treatment of swimming pools.